PERSEPSI PASIEN DI PUSKESMAS KOTA SEMARANG TERHADAP PENDAFTARAN ONLINE SEBAGAI IMPLIKASI SMART CITY - Enny Rachmani (Dian Nuswantoro Semarang, 2020)
Semarang has implemented Smart City for public service. One of the programs was also registration online in primary health care. This study had objectives to describe the perception of primary health care patients about online registration. This research distributed a questionnaire to 800 respondents from 8 of 37 primary health care centers (PHC) consist of 3 PHCs with online registration and 5 PHCs without online registration. The results revealed that 24.6% of patients do not have an internet connection on the mobile phone, and 33.6% never used computers. The computer and internet skills also not so well. Patients choose platform for online registration as SMS (72.4%), internet (62.6%) dan android 41.3 (52.4%). Patients had a positive perception about registration online, 69.9% of patients need online registration and 64.2% will use online registration. Socialization should be done intensively to disseminate the online registration to the patients. Keywords: eHealth, online registration, primary health care